2018
DOI: 10.1002/jper.18-0132
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin is highly expressed in patients with chronic periodontitis and protects against experimental periodontitis in rats

Abstract: These findings suggest that progranulin is highly expressed in the gingiva and GCF of patients with CP and protects against experimental periodontitis in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…However, the mechanism and specific role of TNFRs in PGRN mediated inhibition of M1 polarization remains to be explored. Besides, though we have shown that PGRN protects against experimental periodontitis [30] and promotes inflammatory periodontal bone defect regeneration in rats [31], whether this in vivo efficacy of PGRN is related to anti-M1 polarization waits for investigation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, the mechanism and specific role of TNFRs in PGRN mediated inhibition of M1 polarization remains to be explored. Besides, though we have shown that PGRN protects against experimental periodontitis [30] and promotes inflammatory periodontal bone defect regeneration in rats [31], whether this in vivo efficacy of PGRN is related to anti-M1 polarization waits for investigation.…”
Section: Discussionmentioning
confidence: 91%
“…Plenty of studies indicate that macrophages, when as M1 phenotype, play a vital role in onset and development of periodontitis [34], while PGRN, identified as an endogenous antagonist of TNF-α by competitively binding to TNFRs, has potential positive action in autoimmune and inflammatory diseases, such as osteoarthritis [35] and periodontitis [30]. In this study, we demonstrated that rPGRN inhibited LPS-induced macrophage M1 polarization and these effects were associated with NF-кB and MAPK pathway inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were recruited from April 2018 to August 2018 in Cangzhou Central Hospital. CP patients were selected strictly following the criteria described previously by Li et al 20 All the patients were age ≥ 21 years and the presence of at least 20 teeth. CP patients should have multiple sites with a probing depth (PD) of ≥ 5 mm, attachment loss (AL) of ≥ 2 mm and bone loss confirmed by radiography.…”
Section: Methodsmentioning
confidence: 99%
“…However, anti‐inflammation and osteogenesis promotion by PGRN in periodontitis condition has been seldom investigated. Our recent studies indicated that PGRN was highly expressed in the gingiva and gingival crevicular fluid of patients with chronic periodontitis and exogenous PGRN could protect against experimental periodontitis in rats ; and PGRN could promote regeneration of inflammatory periodontal bone defect in rats via anti‐inflammation, osteoclastogenic inhibition, and osteogenic promotion . For deeper insight of the underlying mechanism of PGRN in improving periodontal regeneration, the present study was conducted to investigate the role of TNFR1 and TNFR2 as well as the underlying signaling pathways in the process of hPDLSCs osteogenic differentiation promoted by PGRN with or without TNF‐α stimulation.…”
Section: Introductionmentioning
confidence: 97%